Dampak pembelajaran berbasis proyek yang berorientasi pada pembelajaran mendalam dan otonomi pembelajar terhadap kemampuan berbicara bahasa Inggris siswa - Anom Sri Ayu Sukariani; Anak Agung Gede Agung; Ni Luh Gede Erni Sulindawati (Indonesian Counselor Association (IKI), 2025)
This research employed a quasi-experimental design. The population consisted of 180 tenth-grade students of the Construction and Building Technology program at SMK Negeri 1 Denpasar in the 2025/2026 academic year. A total of 144 students were selected as samples using cluster random sampling. Data were collected through a speaking performance test to measure English speaking skills and a questionnaire to assess learner autonomy. Data were analyzed using two-way analysis of variance followed by Tukey’s post hoc test. The results showed that: (1) there was a significant difference in English speaking skills between students taught using Deep Learning–oriented PjBL and those taught using conventional instruction at SMKN 1 Denpasar (F = 21.755; p = 0.000); (2) there was a significant difference in English speaking skills between students with high and low learner autonomy (F = 23.412; p = 0.000); (3) there was a significant interaction between Deep Learning–oriented PjBL and learner autonomy on students’ English speaking skills (F = 188.546; p = 0.000); (4) there was no significant difference in English speaking skills between students taught using Deep Learning–oriented PjBL and students with high learner autonomy (Q = 0.12 < Q table = 2.86); (5) there was a significant difference in English speaking skills between students taught using conventional instruction and students with high learner autonomy (Q = 6.72 > Q table = 2.86); and (6) there was a significant difference in English speaking skills between students taught using Deep Learning–oriented PjBL and students with learner autonomy.